A glimpse into the culinary practices of Indus Valley Civilization: a pottery case study from Bagasra (Gola Dhoro) - Sarkar, Siddhant (Πανεπιστήμιο Πελοποννήσου, 2023)
The Indus Valley Civilization (3300 BCE to 1500 BCE) site of Gola Dhoro or Bagasra (Gujarat, India) is located 1 km from the Gulf of Kachch and links the three different and culturally rich regions of Gujarat- Kutch, Saurashtra, and North Gujarat, making it a significant site in the broader region. Concomitantly, four phases were stratigraphically recorded, with sufficient evidence of interaction with other contemporary Chalcolithic Cultures. The present study focuses on the analysis of a pottery assemblage of 72 samples from the site using LED, SEM/EDS, and FTIR to investigate pottery manufacturing techniques and dietary practises. The analysis allowed us to determine the relationship between different wares and shapes, the nature of organic residues and best practises for their study, the relationship between organic residues and vessel typology (i.e., preference of a particular vessel for a specific dietary component), and its distribution in time (different phases) and space (inside and outside the fortification wall). Ultimately, the present project aims to facilitate the synthesis of existing knowledge about the Indus Valley Civilization’s ceramic technology and dietary practises with that of the present study to create a new narrative.
Keywords: Πολιτισμός του Ινδού; Εποχή του Χαλκού -- Νότια Ασία; Κεραμική, Αρχαία -- Ινδία; Οργανικές ενώσεις -- Ανάλυση; Υλικός πολιτισμός -- Ανάλυση; Αρχαιότητες -- Ανάλυση; Αρχαιολογία -- Μεθοδολογία; Indus Valley Civilization; Pottery; Organic residue analysis; FTIR; SEM-EDS; Πολιτισμός της κοιλάδας του Ινδού; Κεραμική; Ανάλυση οργανικών καταλοίπων; Φασματοσκοπία υπέρυθρου μετασχηματισμού Fourier; Ηλεκτρονική μικροσκοπία σάρωσης